A high temperature resistant fracturing fluid and preparation method thereof
By adding crosslinking agent made of green tea leaves and waste borosilicate glass to the fracturing liquid, a crosslinking structure with antioxidant and thermal stability is formed, the problem of easy degradation of existing fracturing liquid at high temperatures is solved, and its performance is significantly improved.
Patent Information
- Application Number
- CN202510279915.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-11
- Publication Date
- 2025-04-08
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing fracturing fluid is prone to degradation under high temperature conditions, resulting in a decrease in viscosity, destroying the cross-linking structure, and affecting the performance of use.
A high-temperature resistant fracturing liquid is adopted, which includes guar hydroxypropyl trimethylammonium chloride, potassium chloride, montmorillonite, nanocellulose, crosslinking agent, additives and stabilizers. The crosslinking agent is made of green tea leaves, waste borosilicate glass and zinc sulfate solution. Through the combination of pretreatment and specific proportions, a crosslinking structure with antioxidant and thermal stability is formed.
It extends the effective action time of the fracturing fluid and improves its performance under high temperature conditions, including improving viscosity stability and reducing filtration loss.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fracturing fluid, in particular to a high temperature resistant fracturing fluid and a preparation method thereof. Background Art
[0002] Fracturing fluid is a working fluid used in oil and gas well fracturing operations. It has the functions of creating fractures, carrying sand, and reducing filtration loss. It can form cracks in oil and gas layers, improve oil and gas permeability, and thus increase oil and gas production.
[0003] In the prior art, fracturing fluid is easily degraded under high temperature, which reduces its viscosity, destroys the cross-linked structure of the fracturing fluid, and affects the performance of the fracturing fluid. Based on this, the present invention provides a high temperature resistant fracturing fluid and a preparation method thereof. Summary of the invention
[0004] The purpose of the present invention is to provide a high temperature resistant fracturing fluid and a preparation method thereof. The high temperature resistant fracturing fluid prepared by the present invention has good high temperature resistance and effectively improves the performance of the fracturing fluid.
[0005] To achieve the above object, the present invention provides the following technical solutions: In a first aspect, the present invention provides a high temperature resistant fracturing fluid, comprising the following raw materials in weight percentage: 1-3% guar hydroxypropyltrimethylammonium chloride, 0.6-1% potassium chloride, 1-3% montmorillonite, 0.4-0.8% nanocellulose, 0.6-1.2% cross-linking agent, 0.04-0.1% regulator, 0.6-1% additive, 0.04-0.1% stabilizer, and the balance is water; The cross-linking agent is composed of the following raw materials: green tea leaves, waste borosilicate glass, and zinc sulfate solution, and both the green tea leaves and the waste borosilicate glass are pre-treated; The additives are composed of the following raw materials: bauxite, magnesite, corn starch, kyanite and andalusite.
[0006] Furthermore, the pretreatment method of the green tea leaves is: fresh green tea leaves are selected, and the green tea leaves are soaked in clean water for 10 to 20 minutes, and the water is drained after soaking, and the green tea leaves are put into an oven, and the oven is set at 50 to 60° C. for drying for 10 to 20 minutes, and then ground into powder after drying to obtain a first powder with a grinding particle size of 10 to 30 μm.
[0007] Furthermore, the pretreatment method of the waste borosilicate glass is: recovering waste borosilicate glass fragments from a glass factory, screening the waste borosilicate glass to remove impurities, immersing it in an ultrasonic cleaning machine, adding a degreasing agent, ultrasonic cleaning for 20 to 30 minutes, and then sending it to a ball mill for grinding. After grinding, it is sent to an oven, and the oven is set at 160 to 180° C. for drying for 10 to 20 minutes to obtain a second powder with a grinding particle size of 10 to 30 μm.
[0008] Furthermore, the cross-linking agent is prepared by the following method: the first powder is mixed with an ethanol solution, the mass concentration of the ethanol solution is 50-70%, the mass ratio of the first powder to ethanol is 1: (10-12), the obtained mixture is stirred evenly, and then refluxed and extracted in a water bath at 75-85°C for 3-5 times, each time for 40-60 minutes, and then the extracts are combined, and the ethanol is recovered by vacuum distillation to obtain an extract, and the extract is sent to an oven, and the oven is set at 55-65°C for drying for 6-10 minutes to obtain a third powder.
[0009] Furthermore, the third powder is mixed with the second powder and added to a reactor, the mass ratio of the third powder to the second powder is 1:(0.4-0.6), deionized water is added to the reactor, the mass of the deionized water is 2-3 times the mass of the third powder, sodium hydroxide is added to adjust the pH value to 9.3-9.5, the reactor is set to heat up to 55-65°C, the speed is 120-160r / min, and the mixture is kept warm and stirred for 2-3h, zinc sulfate solution is added to the reactor, the reactor is set to heat up to 65-75°C, the speed is 200-300r / min, and the mixture is kept warm and stirred for 40-50min to obtain a cross-linking agent.
[0010] Furthermore, the mass concentration of the zinc sulfate solution is 0.04-0.08%, and the mass of the zinc sulfate solution is 1-3% of the mass of the third powder.
[0011] Furthermore, the mass ratio of the bauxite, magnesite, corn starch, kyanite and andalusite is 1:(2-3):(3-4):(0.4-0.8):(0.4-0.8), and the bauxite, magnesite, kyanite and andalusite are all powders with a particle size of 10-20 μm.
[0012] Furthermore, the additive is prepared by the following method: bauxite and magnesite are added to a reactor, the reactor is set to 200-300 r / min and stirred for 10-20 min, then corn starch, kyanite, andalusite and water are added, the mass of the water is 4-6 times the mass of the bauxite, the reactor is set to heat up to 60-70°C, the speed is 200-300 r / min, and the reactor is kept warm and stirred for 20-30 min to prepare the additive.
[0013] Furthermore, the regulator is selected from any one of sodium bisulfate, sodium sulfite, and anthranilic acid, and the stabilizer is selected from sodium tetraborate.
[0014] In a second aspect, the present invention also provides a method for preparing a high temperature resistant fracturing fluid, comprising the following steps: S1: Weigh guar gum hydroxypropyltrimethylammonium chloride, potassium chloride and montmorillonite as needed, mix them, heat them in a water bath to 60-70° C., keep them warm for 6-8 minutes, and subject the obtained product to ultrasonic oscillation treatment for 12-16 minutes to obtain a mixture; S2: The mixture is added into a mixer, nanocellulose, cross-linking agent, regulator, additive and stabilizer are weighed and added into the mixer as required, and the mixer is set at 1000-1200 r / min for stirring for 10-20 min to obtain a high temperature resistant fracturing fluid.
[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. In the present invention, a cross-linking agent is added during the preparation of a high-temperature resistant fracturing fluid. The cross-linking agent is prepared by pre-treating green tea leaves and waste borosilicate glass as main raw materials, and then utilizing tea polyphenols contained in green tea leaves and borosilicate components contained in waste borosilicate glass. The antioxidant effect of tea polyphenols and the thermal stability of borosilicate complement each other. Tea polyphenols inhibit oxidation reactions, protect polymers and borosilicate cross-linked structures from free radical attacks, and reduce the impact of high temperature on the performance of the fracturing fluid, thereby extending the effective action time of the fracturing fluid and improving the use effect of the fracturing fluid.
[0016] 2. In the present invention, by adding cross-linking agents and additives during the preparation of high-temperature resistant fracturing fluid, the cross-linking agents and additives contain a variety of fine particle powders, which can play a role in increasing the specific surface area. Bauxite and magnesite can fill cracks and reduce the filtration loss of fracturing fluid. The high-temperature phase change characteristics of kyanite and andalusite can form a thermal barrier layer in the fracturing fluid to delay high-temperature degradation. Corn starch is used as a natural adhesive to enhance the suspension stability of particles, thereby effectively improving the performance of the fracturing fluid. DETAILED DESCRIPTION
[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0018] It should be noted that the raw materials used in the following examples are all commercially available raw materials.
[0019] Example 1: A high temperature resistant fracturing fluid, comprising the following raw materials in weight percentage: 1% guar gum hydroxypropyltrimethylammonium chloride, 0.6% potassium chloride, 1% montmorillonite, 0.4% nanocellulose, 0.6% cross-linking agent, 0.04% regulator, 0.6% additive, 0.04% stabilizer, and the balance is water; The cross-linking agent is composed of the following raw materials: green tea leaves, waste borosilicate glass, and zinc sulfate solution. The green tea leaves and waste borosilicate glass are both pre-treated; The additives are composed of the following raw materials: bauxite, magnesite, corn starch, kyanite and andalusite.
[0020] The pretreatment method of green tea leaves is as follows: fresh green tea leaves are selected, and the green tea leaves are soaked in clean water for 10 minutes. After soaking, the water is drained and the leaves are put into an oven, and the oven is set at 50° C. for drying for 10 minutes. After drying, the leaves are ground to obtain a first powder with a grinding particle size of 10 μm.
[0021] The pretreatment method of waste borosilicate glass is as follows: waste borosilicate glass fragments are recovered from the glass factory, the waste borosilicate glass is screened to remove impurities, immersed in an ultrasonic cleaning machine, a degreasing agent is added, and ultrasonic cleaning is performed for 20 minutes, and then sent to a ball mill for grinding, and then sent to an oven after grinding, and the oven is set at 160°C for drying for 10 minutes to obtain a second powder with a grinding particle size of 10 μm.
[0022] The cross-linking agent is prepared by the following method: a first powder is mixed with an ethanol solution, the mass concentration of the ethanol solution is 50%, the mass ratio of the first powder to ethanol is 1: (10), the obtained mixture is stirred evenly and then refluxed in a water bath at 75°C for 3 times, each time for 40 minutes, then the extracts are combined, and the ethanol is recovered by vacuum distillation to obtain an extract, and the extract is sent to an oven, and the oven is set at 55°C for drying for 6 minutes to obtain a third powder.
[0023] The third powder and the second powder are mixed and added to the reactor, the mass ratio of the third powder to the second powder is 1: (0.4), deionized water is added to the reactor, the mass of the deionized water is twice the mass of the third powder, sodium hydroxide is added to adjust the pH value to 9.3, the reactor is set to heat up to 55°C, the speed is 120r / min, and the heat preservation and stirring are carried out for 2h, zinc sulfate solution is added to the reactor, the reactor is set to heat up to 65°C, the speed is 200r / min, and the heat preservation and stirring are carried out for 40min to obtain a cross-linking agent.
[0024] The mass concentration of the zinc sulfate solution is 0.04%, and the mass of the zinc sulfate solution is 1% of the mass of the third powder.
[0025] The mass ratio of bauxite, magnesite, corn starch, kyanite and andalusite is 1:(2):(3):(0.4):(0.4). Bauxite, magnesite, kyanite and andalusite are all powders with a particle size of 10 μm.
[0026] The additive is prepared by the following method: bauxite and magnesite are added to a reactor, the reactor is set to 200r / min and stirred for 10min, then corn starch, kyanite, andalusite and water are added, the mass of water is 4 times the mass of bauxite, the reactor is set to heat up to 60°C, the speed is 200r / min, and the reactor is kept warm and stirred for 20min to prepare the additive.
[0027] Sodium bisulfate is used as the regulator and sodium tetraborate is used as the stabilizer.
[0028] A method for preparing a high temperature resistant fracturing fluid comprises the following steps: S1: Weigh guar gum hydroxypropyltrimethylammonium chloride, potassium chloride and montmorillonite as needed, mix them, heat them in a water bath to 60° C., keep them warm for 6 minutes, and subject the obtained product to ultrasonic oscillation treatment for 12 minutes to obtain a mixture; S2: The mixture is added into a mixer, nanocellulose, cross-linking agent, regulator, additive and stabilizer are weighed and added into the mixer as required, and the mixer is set at 1000 r / min for stirring for 10 minutes to obtain a high temperature resistant fracturing fluid.
[0029] Example 2: A high temperature resistant fracturing fluid, comprising the following raw materials in weight percentage: 2% guar gum hydroxypropyltrimethylammonium chloride, 0.8% potassium chloride, 2% montmorillonite, 0.6% nanocellulose, 0.9% cross-linking agent, 0.07% regulator, 0.8% additive, 0.07% stabilizer, and the balance is water; The cross-linking agent is composed of the following raw materials: green tea leaves, waste borosilicate glass, and zinc sulfate solution. The green tea leaves and waste borosilicate glass are both pre-treated; The additives are composed of the following raw materials: bauxite, magnesite, corn starch, kyanite and andalusite.
[0030] The pretreatment method of green tea leaves is as follows: fresh green tea leaves are selected, and the green tea leaves are soaked in clean water for 15 minutes. After soaking, the water is drained and the leaves are put into an oven, and the oven is set at 55° C. for drying for 15 minutes. After drying, the leaves are ground to obtain a first powder with a grinding particle size of 20 μm.
[0031] The pretreatment method of waste borosilicate glass is as follows: waste borosilicate glass fragments are recovered from the glass factory, the waste borosilicate glass is screened to remove impurities, immersed in an ultrasonic cleaning machine, a degreasing agent is added, and ultrasonic cleaning is performed for 25 minutes, and then sent to a ball mill for grinding, and then sent to an oven after grinding, and the oven is set at 170°C for drying for 15 minutes to obtain a second powder with a grinding particle size of 20 μm.
[0032] The cross-linking agent is prepared by the following method: a first powder is mixed with an ethanol solution, the mass concentration of the ethanol solution is 60%, the mass ratio of the first powder to ethanol is 1: (11), the obtained mixture is stirred evenly and then refluxed in a water bath at 80°C for 4 times, each time for 50 minutes, then the extracts are combined, and the ethanol is recovered by vacuum distillation to obtain an extract, and the extract is sent to an oven, and the oven is set at 60°C for drying for 8 minutes to obtain a third powder.
[0033] The third powder and the second powder are mixed and added to the reactor, the mass ratio of the third powder to the second powder is 1: (0.5), deionized water is added to the reactor, the mass of the deionized water is 2.5 times the mass of the third powder, sodium hydroxide is added to adjust the pH value to 9.4, the reactor is set to heat up to 60°C, the speed is 140r / min, and the heat is kept stirring for 2.5h, zinc sulfate solution is added to the reactor, the reactor is set to heat up to 70°C, the speed is 250r / min, and the heat is kept stirring for 45min to obtain a cross-linking agent.
[0034] The mass concentration of the zinc sulfate solution is 0.06%, and the mass of the zinc sulfate solution is 2% of the mass of the third powder.
[0035] The mass ratio of bauxite, magnesite, corn starch, kyanite and andalusite is 1:(2.5):(3.5):(0.6):(0.6). Bauxite, magnesite, kyanite and andalusite are all powders with a particle size of 15 μm.
[0036] The additive is prepared by the following method: bauxite and magnesite are added to a reactor, the reactor is set to 250r / min and stirred for 15 minutes, then corn starch, kyanite, andalusite and water are added, the mass of water is 5 times the mass of bauxite, the reactor is set to heat up to 65°C, the speed is 250r / min, and the reactor is kept warm and stirred for 25 minutes to prepare the additive.
[0037] The regulator is sodium sulfite and the stabilizer is sodium tetraborate.
[0038] A method for preparing a high temperature resistant fracturing fluid comprises the following steps: S1: Weigh guar gum hydroxypropyltrimethylammonium chloride, potassium chloride and montmorillonite as needed, mix them, heat them in a water bath to 65° C., keep them warm for 7 minutes, and subject the obtained product to ultrasonic oscillation treatment for 14 minutes to obtain a mixture; S2: The mixture is added into a mixer, nanocellulose, cross-linking agent, regulator, additive and stabilizer are weighed and added into the mixer as required, and the mixer is set at 1100 r / min and stirred for 15 minutes to obtain a high temperature resistant fracturing fluid.
[0039] Example 3: A high temperature resistant fracturing fluid, comprising the following raw materials in weight percentage: 3% guar gum hydroxypropyltrimethylammonium chloride, 1% potassium chloride, 3% montmorillonite, 0.8% nanocellulose, 1.2% cross-linking agent, 0.1% regulator, 1% additive, 0.1% stabilizer, and the balance is water; The cross-linking agent is composed of the following raw materials: green tea leaves, waste borosilicate glass, and zinc sulfate solution. The green tea leaves and waste borosilicate glass are both pre-treated; The additives are composed of the following raw materials: bauxite, magnesite, corn starch, kyanite and andalusite.
[0040] The pretreatment method of green tea leaves is as follows: fresh green tea leaves are selected, and the green tea leaves are soaked in clean water for 20 minutes. After soaking, the water is drained and the leaves are put into an oven, and the oven is set at 60° C. for drying for 20 minutes. After drying, the leaves are ground to obtain a first powder with a grinding particle size of 30 μm.
[0041] The pretreatment method of waste borosilicate glass is as follows: waste borosilicate glass fragments are recovered from the glass factory, the waste borosilicate glass is screened to remove impurities, immersed in an ultrasonic cleaning machine, a degreasing agent is added, and ultrasonic cleaning is performed for 30 minutes, and then sent to a ball mill for grinding, and then sent to an oven after grinding, and the oven is set at 180°C for drying for 20 minutes to obtain a second powder with a grinding particle size of 30 μm.
[0042] The cross-linking agent is prepared by the following method: a first powder is mixed with an ethanol solution, the mass concentration of the ethanol solution is 70%, the mass ratio of the first powder to ethanol is 1: (12), the obtained mixture is stirred evenly and then extracted under reflux in a water bath at 85°C for 5 times, each time for 60 minutes, then the extracts are combined, and the ethanol is recovered by vacuum distillation to obtain an extract, and the extract is sent to an oven, and the oven is set at 65°C for drying for 10 minutes to obtain a third powder.
[0043] The third powder and the second powder are mixed and added to the reactor, the mass ratio of the third powder to the second powder is 1: (0.6), deionized water is added to the reactor, the mass of the deionized water is 3 times the mass of the third powder, sodium hydroxide is added to adjust the pH value to 9.5, the reactor is set to heat up to 65°C, the speed is 160r / min, and the heat is kept stirring for 3h, zinc sulfate solution is added to the reactor, the reactor is set to heat up to 75°C, the speed is 300r / min, and the heat is kept stirring for 50min to obtain a cross-linking agent.
[0044] The mass concentration of the zinc sulfate solution is 0.08%, and the mass of the zinc sulfate solution is 3% of the mass of the third powder.
[0045] The mass ratio of bauxite, magnesite, corn starch, kyanite and andalusite is 1:(3):(4):(0.8):(0.8). Bauxite, magnesite, kyanite and andalusite are all powders with a particle size of 20 μm.
[0046] The additive is prepared by the following method: bauxite and magnesite are added to a reactor, the reactor is set to 300r / min and stirred for 20min, then corn starch, kyanite, andalusite and water are added, the mass of water is 6 times the mass of bauxite, the reactor is set to heat up to 70°C, the speed is 300r / min, and the reactor is kept warm and stirred for 30min to prepare the additive.
[0047] The regulator is o-aminobenzoic acid and the stabilizer is sodium tetraborate.
[0048] A method for preparing a high temperature resistant fracturing fluid comprises the following steps: S1: Weigh guar gum hydroxypropyltrimethylammonium chloride, potassium chloride and montmorillonite as needed, mix them, heat them in a water bath to 70° C., keep them warm for 8 minutes, and subject the obtained product to ultrasonic oscillation treatment for 16 minutes to obtain a mixture; S2: The mixture is added into a mixer, nanocellulose, cross-linking agent, regulator, additive and stabilizer are weighed and added into the mixer as required, and the mixer is set at 1200 r / min and stirred for 20 minutes to obtain a high temperature resistant fracturing fluid.
[0049] Comparative Example 1: The difference between this comparative example and Example 1 is that in this comparative example, an equal amount of kyanite powder is used to replace the cross-linking agent.
[0050] Comparative Example 2: The difference between this comparative example and Example 1 is that in this comparative example, an equal amount of corn starch is used to replace the additive.
[0051] Comparative Example 3: The difference between this comparative example and Example 1 is that this comparative example does not contain a cross-linking agent.
[0052] Comparative Example 4: This comparative example is different from Example 1 in that: this comparative example does not contain any additives.
[0053] Performance test: The high temperature resistant fracturing fluids prepared in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 were subjected to performance tests, and the obtained test data are recorded in the following table:
[0054] In the performance test, shear viscosity and density tests were performed on the high temperature resistant fracturing fluids prepared in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 at 200°C.
[0055] It can be seen that the shear viscosity and density properties of the high temperature resistant fracturing fluids prepared in Comparative Examples 1, 2, 3 and 4 are lower than those in Examples 1, 2 and 3 under high temperature conditions; this indicates that: by adding a cross-linking agent in the preparation process of the high temperature resistant fracturing fluid, the cross-linking agent is pre-treated and added with green tea leaves and waste borosilicate glass as the main raw materials, and the tea polyphenols contained in the green tea leaves and the borosilicate components contained in the waste borosilicate glass are utilized, wherein the antioxidant effect of tea polyphenols and the thermal stability of borosilicate are complemented with each other, tea polyphenols inhibit oxidation reactions, protect the polymer and the borosilicate cross-linking structure from free radical attacks, and reduce Due to the influence of high temperature on the performance of fracturing fluid, the effective action time of fracturing fluid is prolonged and the use effect of fracturing fluid is improved. By adding cross-linking agent and additives in the preparation process of high temperature resistant fracturing fluid, the presence of a variety of fine particle powders in cross-linking agent and additives can play a role in increasing specific surface area. Bauxite and magnesite can fill cracks and reduce the filtration loss of fracturing fluid. The high temperature phase change characteristics of kyanite and andalusite can form a thermal barrier layer in the fracturing fluid to delay high temperature degradation. Corn starch is used as a natural adhesive to enhance the suspension stability of particles and effectively improve the use performance of fracturing fluid.
[0056] By comparing and analyzing the relevant data in the table, it can be seen that the high temperature resistant fracturing fluid prepared by the present invention has good high temperature resistance. This shows that the high temperature resistant fracturing fluid and the preparation method thereof provided by the present invention have a broader market prospect and are more suitable for promotion.
[0057] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0058] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A high temperature resistant fracturing fluid, characterized in that: The invention comprises the following raw materials in percentage by weight: 1-3% guar gum hydroxypropyltrimethylammonium chloride, 0.6-1% potassium chloride, 1-3% montmorillonite, 0.4-0.8% nanocellulose, 0.6-1.2% cross-linking agent, 0.04-0.1% regulator, 0.6-1% additive, 0.04-0.1% stabilizer, and the balance is water; The cross-linking agent is composed of the following raw materials: green tea leaves, waste borosilicate glass, and zinc sulfate solution, and both the green tea leaves and the waste borosilicate glass are pre-treated; The additive is composed of the following raw materials: bauxite, magnesite, corn starch, kyanite and andalusite.
2. The high temperature resistant fracturing fluid according to claim 1, characterized in that: The green tea leaf pretreatment method comprises the following steps: selecting fresh green tea leaves, soaking the green tea leaves in clean water for 10 to 20 minutes, draining the water after soaking, putting the green tea leaves into an oven, setting the oven at 50 to 60° C. for drying for 10 to 20 minutes, and grinding the green tea leaves after drying to obtain a first powder, wherein the powder particle size is 10 to 30 μm.
3. The high temperature resistant fracturing fluid according to claim 2, characterized in that: The pretreatment method of the waste borosilicate glass is as follows: waste borosilicate glass fragments are recovered from a glass factory, the waste borosilicate glass is screened to remove impurities, immersed in an ultrasonic cleaning machine, a degreasing agent is added, ultrasonic cleaning is performed for 20 to 30 minutes, and then the waste borosilicate glass is sent to a ball mill for grinding, and the ground waste is sent to an oven, the oven is set at 160 to 180° C. for drying for 10 to 20 minutes to obtain a second powder, and the powder particle size is 10 to 30 μm.
4. The high temperature resistant fracturing fluid according to claim 3, characterized in that: The cross-linking agent is prepared by the following method: the first powder is mixed with an ethanol solution, the mass concentration of the ethanol solution is 50-70%, the mass ratio of the first powder to ethanol is 1:(10-12), the obtained mixture is stirred evenly, and then refluxed and extracted in a water bath at 75-85°C for 3-5 times, each time for 40-60 minutes, then the extracts are combined, and the ethanol is recovered by vacuum distillation to obtain an extract, and the extract is sent to an oven, and the oven is set at 55-65°C for drying for 6-10 minutes to obtain a third powder.
5. The high temperature resistant fracturing fluid according to claim 4, characterized in that: The third powder and the second powder are mixed and added to a reactor, the mass ratio of the third powder to the second powder is 1:(0.4-0.6), deionized water is added to the reactor, the mass of the deionized water is 2-3 times the mass of the third powder, sodium hydroxide is added to adjust the pH value to 9.3-9.5, the reactor is set to heat up to 55-65°C, the speed is 120-160r / min, and the reactor is kept warm and stirred for 2-3h, zinc sulfate solution is added to the reactor, the reactor is set to heat up to 65-75°C, the speed is 200-300r / min, and the reactor is kept warm and stirred for 40-50min to obtain a cross-linking agent.
6. The high temperature resistant fracturing fluid according to claim 5, characterized in that: The mass concentration of the zinc sulfate solution is 0.04-0.08%, and the mass of the zinc sulfate solution is 1-3% of the mass of the third powder.
7. The high temperature resistant fracturing fluid according to claim 1, characterized in that: The mass ratio of the bauxite, magnesite, corn starch, kyanite and andalusite is 1:(2-3):(3-4):(0.4-0.8):(0.4-0.8). The bauxite, magnesite, kyanite and andalusite are all powders with a particle size of 10-20 μm.
8. The high temperature resistant fracturing fluid according to claim 1, characterized in that: The additive is prepared by the following method: bauxite and magnesite are added into a reactor, the reactor is set to stir at 200-300 r / min for 10-20 min, corn starch, kyanite, andalusite and water are then added, the mass of the water is 4-6 times the mass of the bauxite, the reactor is set to heat up to 60-70°C, the speed is 200-300 r / min, the reactor is kept warm and stirred for 20-30 min to prepare the additive.
9. The high temperature resistant fracturing fluid according to claim 1, characterized in that: The regulator is selected from any one of sodium bisulfate, sodium sulfite and anthranilic acid, and the stabilizer is selected from sodium tetraborate.
10. A method for preparing a high temperature resistant fracturing fluid according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1: Weigh guar gum hydroxypropyltrimethylammonium chloride, potassium chloride and montmorillonite as needed, mix them, heat them in a water bath to 60-70° C., keep them warm for 6-8 minutes, and subject the obtained product to ultrasonic oscillation treatment for 12-16 minutes to obtain a mixture; S2: The mixture is added into a mixer, nanocellulose, cross-linking agent, regulator, additive and stabilizer are weighed and added into the mixer as required, and the mixer is set at 1000-1200 r / min for stirring for 10-20 min to obtain a high temperature resistant fracturing fluid.